Environmental Adult Education and Environmentally-Friendly Fishing in Rivers State - Dr. Kpeno Amon Ephraim (International Journal on Integrated Education, 2022)
This paper seeks to examined the position of Environmental Adult Education in the adoption of environmentally-friendly methods of fishing in Rivers State of Nigeria. It seeks to review the concept of fishing and environmentally-friendly methods of fishing; identify the challenges faced by the fisheries industries in Nigeria; effects of fishing and fishing methods on the ecosystem; environmentally-friendly methods of fishing; ways to reduce fishing effort to sustainable levels; ways to optimise the catches of target species and minimise unwanted catches; ways to reduce the impact of fishing on habitat; ways to balance environmental and economic sustainability and environmentally-unfriendly methods of fishing. The paper revealed that the environmentally-unfriendly methods of fishing are fishing with nets with tiny holes among other things, have been discovered as their environmentally-unfriendly methods of fishing. The paper discovered that EAE needs to be taught to the adult population so that they may acquire the right knowledge to deal friendly with the environment. It was recommended among other things that staff of Rivers State Agricultural Development Programmes (RSADP) should be given environmental adult education to enable them have the knowledge to pass to the fisherfolk in their areas of jurisdiction; in order to promote environmentally-friendly methods of fishing among their clienteles.